2011
DOI: 10.1021/je1012586
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Aqueous Solutions of Piperazine and (2-Amino-2-methyl-1-propanol + Piperazine) from (298.15 to 333.15) K

Abstract: The density (F), viscosity (η), surface tension (σ), and refractive index (n D ) of aqueous solutions of piperazine and aqueous blends of 2-amino-2-methyl-1-propanol (AMP) with piperazine were experimentally measured for a wide range of temperature (298.15 to 333.15) K. The physical properties were measured for piperazine mass fractions (1.74, 3.45, 6.88, and 10.35) and for aqueous blends of (AMP þ PZ) with mass fractions {100 (w 1 /w 2 ) = (28.26/1.74), (26.55/3.45), (23.12/6.88), (19.65/ 10.35)}. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 22 publications
9
27
0
Order By: Relevance
“…The viscosity increases with an increase in the carbon loading of aqueous solutions because of the CO 2 ingestion. And, the viscosity of the virgin and CO 2 -loaded aqueous solution decreases with increasing temperature (DiGuilio et al 1992;Idris et al 2017;Fu et al 2012;Murshid et al 2011;Muhammad et al 2009;Rebolledo-Libreros and Trejo 2006;Samanta and Bandyopadhyay 2006) and is shown in Fig. 8a-c.…”
Section: Effect Of Temperature On Kinematic Viscosity Of Different Carbon-loaded Samplesmentioning
confidence: 91%
See 1 more Smart Citation
“…The viscosity increases with an increase in the carbon loading of aqueous solutions because of the CO 2 ingestion. And, the viscosity of the virgin and CO 2 -loaded aqueous solution decreases with increasing temperature (DiGuilio et al 1992;Idris et al 2017;Fu et al 2012;Murshid et al 2011;Muhammad et al 2009;Rebolledo-Libreros and Trejo 2006;Samanta and Bandyopadhyay 2006) and is shown in Fig. 8a-c.…”
Section: Effect Of Temperature On Kinematic Viscosity Of Different Carbon-loaded Samplesmentioning
confidence: 91%
“…Density, viscosity and surface tension were measured experimentally over a mass fraction of (1.74, 3.45, 6.88 and 10.35) for aqueous solution piperazine with the temperature range of 298.15 to 333.15 K. The results were revealed that the ρ and μ increase with an increase in the mass fraction of piperazine whereas surface tension decreases with an increase in mass fraction. Murshid et al (2011) reported that all thermophysical properties decrease with an increase in temperature. Muhammad et al (2009) determined the thermophysical properties of density, dynamic viscosity and surface tension of aqueous piperazine with mass fractions (1.74, 5.16 and 10.35) and temperature range of 298.15 to 338.15 K. Piperazine has limited solubility with water, and this concept has been explained by the formation of hexahydrate crystals which melts at 317 K. This is reinforced by the appearance of a discontinuity in piperazine (PZ) solubility at around 313 K. The results were exposed that the density and viscosity increase with an increase in the mass fraction of piperazine whereas surface tension decreases with an increase in the mass fraction of PZ.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Experimentally measured data for density were converted into graphical form with respect to temperature, and based on various series of concentrations, the best fit was found by the least-squares method. 32,33 Experimentally measured data for density were converted into graphical form with respect to temperature, and based on various series of concentrations, the best fit was found by the least-squares method.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the correlations of Samanta and Bandyopadhyay (Samanta and Bandyopadhyay, 2006), and Murshid et al (Murshid et al, 2011), were applied to obtain the density ሺߩ ሻ and kinematic viscosity ሺߤ ሻ of aqueous PZ solutions, at various temperatures and amine concentrations. Liquid phase mass transfer coefficient ሺ݇ ሻ, was calculated using the Onda et al (Onda et al, 1968) correlation for randomly packed columns as given in Eq.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%